2019
DOI: 10.14744/nci.2019.17048
|View full text |Cite
|
Sign up to set email alerts
|

Mucınous Endometrial Cancer: Clinical Study of Eleven Cases

Abstract: In this study, we analyzed surgico-pathologic factors of mucinous type endometrial carcinoma and examined its frequency of recurrence. METHODS: In this study, eleven cases, definitely diagnosed as pure mucinous type endometrium carcinoma between January 1993 and May 2013, were reviewed. RESULTS: Of 1640 women with endometrium carcinoma, 11 (0.67%) of them had a mucinous cell type. Mean age of the study group was 55 years. According to the FIGO 2009, 10 (90.9%) cases were evaluated as stage I and 1 (9.1%) as st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Figure 7 shows the "histomics" features with significant alterations between LNM+ and LNM− patients in top-value tiles, enhanced texture, voluminous extracellular mucin, cleft-like structures and elongated angular glandular lumen, which distinguish LNM+ from LNM− patients well. These suggested features from the red subregions appear to be highly consistent with pathologists' experience and previous studies (23)(24)(25). Feature visualization demonstrated that output results of our model have realistic interpretability.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Figure 7 shows the "histomics" features with significant alterations between LNM+ and LNM− patients in top-value tiles, enhanced texture, voluminous extracellular mucin, cleft-like structures and elongated angular glandular lumen, which distinguish LNM+ from LNM− patients well. These suggested features from the red subregions appear to be highly consistent with pathologists' experience and previous studies (23)(24)(25). Feature visualization demonstrated that output results of our model have realistic interpretability.…”
Section: Discussionsupporting
confidence: 86%
“…Enhanced texture, voluminous extracellular mucin, cleftlike structures and elongated angular glandular lumen were "histomics" features with significant alterations between LNM+ and LNM− WSIs, indicating an increased rate of lymph node involvement. These features were consistent with previous studies (23)(24)(25) and provide an interpretative reliability to the predictive results of the AI-model.…”
Section: Interpretation Of Predictive Performance Of the Mil Modelsupporting
confidence: 91%
“…One reason for the high serum CA19-9 level was the marked mucin production from carcinoma cells. Although our patient underwent intravenous chemotherapy for the recurrent tumor in the pelvis, the treatment option might be radiotherapy in a case of recurrent mucinous carcinoma [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…61 Other analyses that have mostly used the International Federation of Gynecology and Obstetrics (FIGO) grading schemes found the grade distribution to be as follows: grade I (average: 69.6%; range: 58% to 80%); grade 2 (average 25.1%; range: 17% to 36.6%); grade 3 (average 7.1%; range: 0% to 11%). 53,54,57,59 The mitotic index for mucinous carcinoma is typically low, with only 29% of cases reaching a maximal mitotic index of 1 mitotic figure/high power field in the Ross et al series. 17 Cells with eosinophilic cells are often admixed, and indeed, there is a possibility that eosinophilic and mucinous change are related in this context, since both display comparably high frequencies of MUC5AC expression.…”
Section: Mucinous Carcinomamentioning
confidence: 97%
“…For the analyses below, unless specifically stated otherwise, reports of mucinous carcinoma before 2020 are presumed to represent MCU. 27,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Mucinous Carcinomas of the Usual Type (1) Frequency: Ross et al 17 53,54,[57][58][59] Most patients presented with postmenopausal bleeding or abdominal pain. 57 Eighty three percent to 100% of patients were Caucasian.…”
Section: Mucinous Carcinomamentioning
confidence: 99%